The informational security of ukraine: legal guarantee and reality of providing - Hrubinko, Andrii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2019)
In the article the peculiarities of legal guarantee of the informational security of Ukraine in the conditions of modern challenges and threats (first of all, the hybrid war of Russia v. Ukraine) are analyzed. Practical aspects and problems of providing of the informational security of Ukraine are revealed.